CARDIOVASCULAR SYSTEM: STRUCTURAL CHARACTERISTICS, AGE-RELATED CHANGES, AND PATHOGENESIS OF DISEASES - Gulnara Raufovna Islamova; Laziza Zokirova (Modern American Journals, 2025)
This study provides a comprehensive overview of the main structures of the heart and cardiovascular system and their functional significance. It includes a detailed analysis of the macro- and microstructural organization of the heart, age-related morphological changes, anatomical variations of the coronary arteries, and key anatomical factors involved in the development of heart failure. The cellular composition of the heart wall layers — endocardium, myocardium, and epicardium — the fibroelastic structure of the heart valves, and the localization and functional characteristics of the conduction system are described based on solid scientific evidence.